Gambaran pewarnaan imunohistokimia S100 pada meningioma di Rumah Sakit Umum Pusat H. Adam Malik Medan - Gatot Aji Prihartomo; Abdul Gofar Sastrodiningrat; Iskandar Japardi; Sufida dr (Fakultas Kedokteran USU, 2013)
Introduction: This study explores and describe the S100 immunohistochemical staining in meningioma.Methods: Sample specimens collected from patients who had meningioma undergo tumor removal surgery in the Adam Malik General Hospital Medan has previously been carried out basic hematoxylin eosin staining and was confirmed as meningioma by Epithelial Membrane Antigene (EMA) imunohystochemical staining. Representative slides are made of paraffin blocks and then performed S100 immunohistochemical staining. Staining intensity (SI) was score on scale 0-3 (from no staining to strong staining). Then viewed the characteristics of gender, age, location of tumor, World Health Organization (WHO) meningioma grade, histopathologictype, and tumor recurrence of meningioma specimens that express S100 immunohistochemical staining.Results: Thirty-one specimens of meningioma classified according to WHO criteria: benign 28/31 (90.3%), atypical 2/31 (6.5%) and anaplastic 1/31 (3.2%). These three criteria are classified according to histopathologic type. Meningothelial meningioma is the most widely histopathological types 17/31 (54.8%). Of the overall sample specimens, only 11/31 (35.5%) specimens expressed S100 immunohistochemical staining, the remaining 20/31 (64.5%) did not express. Of the 11 specimens that express S100 staining, benign meningiomas express 8/28 (28.6%) and fibroblastic meningiomas are the most strong S100 immunohistochemical staining( +3) between all the histopathologic type.Conclusion: In general, the results obtained from this study correspond by previous literature.Keyword: immunohistochemical staining; S100; meningioma